PHENOMENOLOGICAL STUDY ON THE IDENTITY AND PERSPECTIVE OF WOMEN JOURNALISTS IN THE CITY OF SURABAYA IN INTERPRETING THE PROFESSION - Vania Shafa Meidina; Merry Fridha Tri Palupi; Teguh Priyo Sadono (Media Inovasi Pendidikan dan Publikasi, 2024)
Women's participation in the media industry is still limited with policy standards varying from media to media, often creating stereotypes to the detriment of women. Indonesia's media industry tends to maintain a traditional view that places women's role in mass media at a lower level and less prioritized. Despite being faced with challenges, obstacles, and double burdens, women journalists remain persistent in maintaining the existence of their profession. This study aims to explore the identity of women journalists in Surabaya City and their perspectives on the meaning of the journalist profession, especially in the media industry of Surabaya City. With qualitative methods and data collection techniques through in-depth interviews, observation, and documentation, this study applies phenomenological approaches and George Herbert Mead's Symbolic Interaction Theory. The results of the study highlight various motives that cause women in interpreting the journalist profession, including being inspired by idols, passion and basic abilities, love of adventure, professional flexibility, personal existence, and as a form of self-proof.